Analytical validation of an ultraviolet–visible procedure for determining lutein concentration and application to lutein-loaded nanoparticles. (1st September 2017) - Silva, Jéssica Thaís do Prado; Silva, Anderson Clayton da; Geiss, Julia Maria Tonin; de Araújo, Pedro Henrique Hermes; Becker, Daniela; Bracht, Lívia; Leimann, Fernanda Vitória; Bona, Evandro; Guerra, Gustavo Petri; Gonçalves, Odinei Hess
Highlights: Concentration of bioactive compounds as lutein in nanoparticles must be well known. Validation of a fast, reliable procedure to quantify lutein in nanoparticles was carried out. It enables to quantify amounts as low as 4.407 mg·L −1 . Abstract: Lutein is a carotenoid presenting known anti-inflammatory and antioxidant properties. Lutein-rich diets have been associated with neurological improvement as well as reduction of the risk of vision loss due to Age-Related Macular Degeneration (AMD). Micro and nanoencapsulation have demonstrated to be effective techniques in protecting lutein against degradation and also in improving its bioavailability. However, actual lutein concentration inside the capsules and encapsulation efficiency are key parameters that must be precisely known when designing in vitro and in vivo tests. In this work an analytical procedure was validated for the determination of the actual lutein content in zein nanoparticles using ultraviolet–visible spectroscopy. Method validation followed the International Conference on Harmonisation (ICH) guidelines which evaluate linearity, detection limit, quantification limit, accuracy and precision. The validated methodology was applied to characterize lutein-loaded nanoparticles.